Differential seed germination of a keystone palm (Euterpe edulis) dispersed by avian frugivores - De Barros Leite, Abraão [UNESP]; Brancalion, Pedro H.S.; Guevara, Roger; Galetti, Mauro [UNESP] (Cambridge University Press (CUP), 2012)
The effectiveness of seed dispersal by vertebrates has been analysed by examining both quantitative and qualitative components (Jordano & Schupp 2000, Schupp et al. 2010). While the quantitative component is relatively easily assessed in the field (e.g. visitation rate, number of fruits eaten per visit), the qualitative component (e.g. fate of dispersed seeds, seed treatment in the digestive system of the disperser) is rarely studied under natural conditions, because it is difficult to measure the effects on seeds once ingested by the dispersers (Cortes et al. 2009). © Cambridge University Press 2012.
Keywords: Aburria cujubi; Atlantic forest; Frugivory; Gut passage time; Pteroglossus bailloni; Ramphastos dicolorus; Ramphastos toco; Ramphastos vitellinus; Seed dispersal; Seed fate; Turdus rufiventris; avifauna; digestive system; evergreen tree; frugivory; germination; keystone species; metabolism; monocotyledon; seed; seed treatment; zoochory; Atlantic Forest; Aburria; Aves; Euterpe edulis; Pteroglossus; Vertebrata